Impact of laboratory cost display on resident attitudes and knowledge about costs. Issue 1092 (31st March 2016) - Long, Theodore; Bongiovanni, Tasce; Dashevsky, Meir; Halim, Andrea; Ross, Joseph S; Fogerty, Robert L; Silvestri, Mark T
Abstract: Aim: Cost awareness has been proposed as a strategy for curbing the continued rise of healthcare costs. However, most physicians are unaware of the cost of diagnostic tests, and interventions have had mixed results. We sought to assess resident physician cost awareness following sustained visual display of costs into electronic health record (EHR) order entry screens. Study Design: We completed a preintervention and postintervention web-based survey. Participants were physicians in internal medicine, paediatrics, combined medicine and paediatrics, obstetrics and gynaecology, emergency medicine, and orthopaedic surgery at one tertiary co are academic medical centre. Costs were displayed in the EHR for 1032 unique laboratory orders. We measured attitudes towards costs and estimates of Medicare reimbursement rates for 11 common laboratory and imaging tests. Results: We received 209 survey responses during the preintervention period (response rate 71.1%) and 194 responses during the postintervention period (response rate 66.0%). The proportion of residents that agreed/strongly agreed that they knew the costs of tests they ordered increased after the cost display (8.6% vs 38.2%; p<0.001). Cost estimation accuracy among residents increased after the cost display from 24.0% to 52.4% for laboratory orders (p<0.001) and from 37.7% to 49.6% for imaging orders (p<0.001). Conclusions: Resident cost awareness and ability to accurately estimate laboratory order costs improved significantly after implementation of a comprehensive EHR cost display for all laboratory orders. The improvement in cost estimation accuracy for imaging orders, which did not have costs displayed, suggested a possible spillover effect generated by providing a cost context for residents.